2015
DOI: 10.1177/1934578x1501001141
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Xanthones from Cratoxylum cochinchinense

Abstract: Chemical investigation of Cratoxylum cochinchinense stem bark has led to the isolation and identification of a new xanthone, cochinchinone M (1), together with 12 known compounds. Their structures were elucidated on the basis of spectroscopic methods, including UV, IR, NMR and MS. Some compounds were evaluated for their antibacterial and acetylcholinesterase inhibitory activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The IR spectrum showed absorption bands due to a hydroxy group and a carbonyl group at ν max 3324 br and 1643 cm −1 , respectively. UV bands were observed at λ max 234, 268, 318, and 384 nm, similar to those of cochinchinone A (7), also isolated in the course of this study, suggesting a 1,3,7-trioxygenated xanthone chromophore [18]. The 1 H NMR (CDCl 3 ) spectrum of 1 showed three aromatic protons with ABC-type signals at δ H 7.37 (1H, d, J = 8.9 Hz, H-5), δ H 7.24 (1H, dd, J = 8.9, 3.1 Hz, H-6), and δ The UV spectrum of 3 exhibited characteristic absorption bands of a xanthone (λ max 202, 236, 264 sh, 308, 364 nm).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The IR spectrum showed absorption bands due to a hydroxy group and a carbonyl group at ν max 3324 br and 1643 cm −1 , respectively. UV bands were observed at λ max 234, 268, 318, and 384 nm, similar to those of cochinchinone A (7), also isolated in the course of this study, suggesting a 1,3,7-trioxygenated xanthone chromophore [18]. The 1 H NMR (CDCl 3 ) spectrum of 1 showed three aromatic protons with ABC-type signals at δ H 7.37 (1H, d, J = 8.9 Hz, H-5), δ H 7.24 (1H, dd, J = 8.9, 3.1 Hz, H-6), and δ The UV spectrum of 3 exhibited characteristic absorption bands of a xanthone (λ max 202, 236, 264 sh, 308, 364 nm).…”
Section: Resultsmentioning
confidence: 73%
“…The extract of C. cochinchinense has a broad spectrum of biological activities [3,4], and the plant is a rich source of xanthones, anthraquinones, and other phenolic compounds [5,6]. Some isolated xanthones have shown antibacterial [7,8], cytotoxic [6,9], and antimalarial [6,10] activities. The most thoroughly studied xanthones are αmangostin and garcinone E, which have been isolated from mangosteen fruit (Garcinia mangostana L, Guttiferae) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have been previously isolated from different organs of G. mangostana [ 36 , 37 , 38 ]. 9-hydroxycalabaxanthone 1 has been found in the Clusiaceae and Hypericaceae families and has been characterized by its anticancer, antioxidant, and ability to inhibit the PL and AG enzymes [ 34 , 39 , 40 ]. 8-deoxygartanin 2 has been reported in other species of the Clusiaceae family and has been found to have anticancer, anti-Alzheimer’s properties, and the ability to inhibit the PL and AG enzymes [ 34 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…9-hydroxycalabaxanthone 1 has been found in the Clusiaceae and Hypericaceae families and has been characterized by its anticancer, antioxidant, and ability to inhibit the PL and AG enzymes [ 34 , 39 , 40 ]. 8-deoxygartanin 2 has been reported in other species of the Clusiaceae family and has been found to have anticancer, anti-Alzheimer’s properties, and the ability to inhibit the PL and AG enzymes [ 34 , 39 , 40 ]. Gartanin 3 has been reported to be found in other species of the Clusiaceae family and multiple studies have shown its anticancer and antitumor properties, and ability to inhibit enzymes such as PL and AA [ 34 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…By comparison with those data from the literatures, the known analogues were identified as cochinchinoxanthone ( 2 ) [21], 1,4,7-trihydroxy-8-methoxyxanthone ( 3 ) [22], gentisein ( 4 ) [23], 1,6-dihydroxy-2,5,8-trimethoxyxanthone ( 5 ) [23], 1,7-dihydroxyxanthone ( 6 ) [24], 1,7-dihydroxy-4-methoxyxanthone ( 7 ) [25], 1,7-dihydroxy-3,6-dimethoxyxanthone ( 8 ) [26], 1,7-dihydroxy-8-methoxyxanthone ( 9 ) [27], 1,5,6-trihydroxy-7-methoxyxanthone ( 10 ) [28], 1,4,7-trihydroxyxanthone ( 11 ) [29], 1,5,6-trihydroxy-3,7-dimethoxyxanthone ( 12 ) [30], 1,3,5,6-tetrahydroxyxanthone ( 13 ) [31], 1,3,6,7-tetrahydroxyxanthone ( 14 ) [32], 1,3,6-trihydroxy-7-methoxyxanthone ( 15 ) [29], cratoxanthone C ( 16 ) [33], 1,2,4-trimethoxy-3,8-dimethoxyxanthone ( 17 ) [34], 1,3,7-trihydroxy-2-(3-methylbut-2-enyl)-xanthone ( 18 ) [35], dulcisxanthone B ( 19 ) [20], cudratricusxanthone E ( 20 ) [36], γ-mangostin ( 21 ) [37], 1,3,7-trihydroxy-2,4-diisoprenylxanthone ( 22 ) [38], cochinchinone A ( 23 ) [33], cochinchinone B ( 24 ) [33], pruniflorone Q ( 25 ) [39], 1,3,5-trihydroxy-6′,6′-dimethyl-2 H -pyrano(2′,3:6,7)xanthone ( 26 ) [30], pruniflorone N ( 27 ) [40], xanthone V 1 ( 28 ) [41], osajaxanthone ( 29 ) [42], cochinchinone I ( 30 ) [43], 1,7-dihydroxy-4-(3,7-dimethylocta-2,6-dienyl)-5′-(1-hydroxy-1-methylethyl)-4′,5′-dihydrofuro[2′,3′:3,2]-xanthone ( 31 ) [44].…”
Section: Resultsmentioning
confidence: 99%